The role of macroprudential policies under carbon pricing - PUNZI, Maria Teresa (Institutional Knowledge at Singapore Management University, 2024)
This paper analyses the effectiveness of macroprudential policy on macro-financial fluctuations when the government enforces carbon pricing to reduce carbon emissions and achieve the net-zero target. A carbon tax policy alone can reduce carbon emissions by 2030, but at the cost of a deep and prolonged recession, with consequential financial instability due to a higher probability of default on entrepreneurs in the brown sector. This result suggests that carbon pricing should be coupled with complementary policies, such as macroprudential policy. In particular, differentiated LTV ratios and differentiated capital requirements that penalize the brown sector in favour of the green sector tend to decrease the probability of default in the green sector and encourage green lending in supporting the transition to a green economy. However, such policies have little contribution in offsetting the negative impact on the macroeconomy. More stringent levels of prudential regulations are needed to reduce the fall in GDP and consumption. More specifically, the “one-for-one” prudential capital requirements on fossil fuel financing can effectively reduce defaults and move to a greener economy.